2020
DOI: 10.1002/zaac.202000076
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structures, Thermal and Luminescence Properties of Zn and Cd Halide Coordination Polymers with 2‐Cyanopyrazine

Abstract: Reaction of MX2 (M = Cd, Zn; X = Cl, Br, I) with 2‐cyanopyrazine leads to the formation of compounds with the composition CdX2(2‐cyanopyrazine)2 (X = Cl; CdCl, X = Br; CdBr and X = I; CdI) and ZnX2(2‐cyanopyrazine)2 (X = Cl; ZnCl, X = Br; ZnBr and X = I; ZnI/I). In the crystal structures of the Cd compounds and in ZnCl, the metal cations are octahedrally coordinated and are linked into chains by the halide anions via common edges. In contrast, in the crystal structures of ZnBr and ZnI/I the metal cations are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…These compounds can also be obtained if the discrete complex CdI 2 (2-methylpyrazine) 2 (H 2 O) is thermally decomposed. In further work we investigated similar compounds with 2-cyanopyrazine as coligand, where we observed a different thermal reactivity as a function of the nature of the halide anions (Jess et al, 2020).…”
Section: Chemical Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds can also be obtained if the discrete complex CdI 2 (2-methylpyrazine) 2 (H 2 O) is thermally decomposed. In further work we investigated similar compounds with 2-cyanopyrazine as coligand, where we observed a different thermal reactivity as a function of the nature of the halide anions (Jess et al, 2020).…”
Section: Chemical Contextmentioning
confidence: 99%
“…We subsequently found that transition-metal halide compounds with twofold positively charged cations such as Cd II that also show a pronounced structural variability can be obtained by this route (Na ¨ther et al, 2017;Jess et al, 2020). In most cases, discrete CdX 2 complexes are observed (Ghanbari et al, 2017;Liu, 2011), but these units can also condense into dinuclear (Santra et al, 2016;Xie et al, 2003) and tetranuclear units (Zhu, 2011) or polymers (Nezhadali Baghan et al, 2021;Satoh et al, 2001), where the latter can be further linked by the coligands into layers (Hu et al, 2009;Marchetti et al, 2011).…”
Section: Chemical Contextmentioning
confidence: 99%